Post-training and mentorship experiences of KidzAlive-trained healthcare workers at primary healthcare facilities in KwaZulu-Natal, South Africa - Chipo Mutambo; Kemist Shumba; Khumbulani W. Hlongwana (AOSIS, 2020)
Background: KidzAlive, a multicomponent, child-centred capacity building model was adopted by South Africa's National Department of Health to address the challenges of quality of care among HIV+ children. This model involves training and mentoring healthcare workers (HCWs) on a child-centred care approach of communicating with children and their primary caregivers (PCGs). This study explored HCWs' post-training experiences after a 6-months implementation period. Aim: To evaluate the KidzAlive model as a healthcare approach that seeks to improve the quality of HIV care among children. Setting: The study was conducted in 20 PHC rural and urban facilities across four districts in KwaZulu-Natal. Methods: Interviews were conducted by trained interviewers who followed a structured interview guide. These were audio-recorded, transcribed, and imported into NVivo 10 software for thematic analysis. Thematic analysis was used to develop a coding framework from the participant's responses. Results: Five themes, namely: (1) increased healthcare worker knowledge, skills and confidence to provide child-friendly HIV services to children; (2) increased involvement of HIV + children in own healthcare journey; (3) the involvement of primary caregivers in children's healthcare journey; (4) improved health outcomes for HIV + children; and e) transformation of the PHC environment towards being more child-friendly. Conclusion: The findings present preliminary evidence of successful KidzAlive trained HCWs' buy-in of KidzAlive intervention. KidzAlive has been well integrated into current service delivery processes in PHC facilities. However, more rigorous research is warranted to fully understand the impact of this intervention on children and their primary caregivers.